Respuesta :

Answer:

=

±

2

4

2

x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}

x=2a−b±b2−4ac​​

Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.

5

2

7

1

8

=

0

5x^{2}-7x-18=0

5x2−7x−18=0

=

5

a={\color{#c92786}{5}}

a=5

=

7

b={\color{#e8710a}{-7}}

b=−7

=

1

8

c={\color{#129eaf}{-18}}

c=−18

=

(

7

)

±

(

7

)

2

4

5

(

1

8

)

Step-by-step explanation:

open up the image so you can see the answer ! hope it helps you :)

Ver imagen melanieredae